Audio-Tactile Rendering: A Review on Technology and Methods to Convey Musical Information through the Sense of Touch. - Remache-Vinueza, Byron; Trujillo-León, Andrés; Zapata, Mireya; Sarmiento-Ortiz, Fabián; Vidal-Verdú, Fernando (MDPI, 2021)
Tactile rendering has been implemented in digital musical instruments (DMIs) to offer the musician haptic feedback that enhances his/her music playing experience. Recently, this implementation has expanded to the development of sensory substitution systems known as haptic music players (HMPs) to give the opportunity of experiencing music through touch to the hearing impaired. These devices may also be conceived as vibrotactile music players to enrich music listening activities. In this review, technology and methods to render musical information by means of vibrotactile stimuli are systematically studied. The methodology used to find out relevant literature is first outlined, and a preliminary classification of musical haptics is proposed. A comparison between different technologies and methods for vibrotactile rendering is performed to later organize the information according to the type of HMP. Limitations and advantages are highlighted to find out opportunities for future research. Likewise, methods for music audio-tactile rendering (ATR) are analyzed and, finally, strategies to compose for the sense of touch are summarized. This review is intended for researchers in the fields of haptics, assistive technologies, music, psychology, and human–computer interaction as well as artists that may make use of it as a reference to develop upcoming research on HMPs and ATR.
Keywords: Música - Ayudas técnicas; Ayudas técnicas para personas con discapacidad; Biosensores; Human computer interaction; Haptic music player; Musical haptics; Musical haptic wearables; Sensory substitution systems; Tactile rendering; Vibrotactile feedback; Vibrotactile music composition